2000
DOI: 10.1007/s100510050064
|View full text |Cite
|
Sign up to set email alerts
|

Growth exponent in the Domany-Kinzel cellular automaton

Abstract: In a roughening process, the growth exponent β describes how the roughness w grows with the time t: w ∼ t β . We determine the exponent β of a growth process generated by the spatiotemporal patterns of the one dimensional Domany-Kinzel cellular automaton. The values obtained for β shows a cusp at the frozen/active transition which permits determination of the transition line. The β value at the transition depends on the scheme used: symmetric (β ∼ 0.83) or non-symmetric (β ∼ 0.61). Using damage spreading ideas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…We construct the BPCA phase diagram, for p 3 = 0 and p 3 = 1, using simulations of systems of up to L = 10000 sites (with periodic boundaries), applying the growth exponent method [22] to locate the transition lines. The initial condition used in the simulations is random, with half the sites occupied.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We construct the BPCA phase diagram, for p 3 = 0 and p 3 = 1, using simulations of systems of up to L = 10000 sites (with periodic boundaries), applying the growth exponent method [22] to locate the transition lines. The initial condition used in the simulations is random, with half the sites occupied.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The surface-growth process is attended by kinetic roughening; the associated critical exponents can be measured [11] following the scaling concepts developed by Family and Vicsék [25]. Atman and Moreira [22] demonstrated that the growth exponent β w exhibits a cusp at criticality, and is very useful for detecting phase transitions.…”
Section: A Surface Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, this approach has been used to study other kinds of models such as cellular automata [9,10,11], sandpiles [12], and the contact process [13]. These studies are done by mapping the model into a growth process which generates an interface -the accumulation method.…”
Section: Introductionmentioning
confidence: 99%